Understanding Women's Preconception Health Goals: Audience Segmentation Strategies for a Preconception Health Campaign. (September 2014) - Lynch, Molly; Squiers, Linda; Lewis, Megan A.; Moultrie, Rebecca; Kish-Doto, Julia; Boudewyns, Vanessa; Bann, Carla; Levis, Denise M.; Mitchell, Elizabeth W.
This article discusses the social marketing planning process and strategies used to design a preconception health campaign, Show Your Love, launched in February 2013. Developing a social marketing strategy for preconception health is a challenging endeavor, in part because preconception health represents a set of diverse behaviors and the audience for the campaign is quite large, encompassing all women of childbearing age whether they intend to become pregnant or not. The network of organizations implementing the campaign, the National Preconception Health Consumer Workgroup, required a broad audience segmentation strategy; therefore, two large audiences were selected. This commentary describes the two primary audiences selected for the campaign based on the Transtheoretical Model—intenders (those in contemplation, preparation, and action) and nonintenders (precontemplators)—and explores how levels of knowledge, motivations, the campaign product, and the campaign goals are distinct for each audience. Additionally, the authors describe potential extensions to the segmentation strategy that could offer finer grained approaches for social marketers who may be building on the Show Your Love campaign or designing other programs in this area.